2021
DOI: 10.1097/mat.0000000000001592
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Membrane Oxygenation Blood Flow and Blood Recirculation Compromise Thermodilution-Based Measurements of Cardiac Output

Abstract: The contribution of veno-venous (VV) extracorporeal membrane oxygenation (ECMO) to systemic oxygen delivery is determined by the ratio of total extracorporeal blood flow (trueQ˙EC) to cardiac output (trueQ˙). Thermodilution-based measurements of trueQ˙ may be compromised by blood recirculating through the ECMO (recirculation fraction; Rf). We measured the effects of trueQ˙EC and Rf on classic thermodilution-based measurements of trueQ˙ in six anesthetized pigs. An ultrasound flow probe measured total aortic bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…In contrast, Gattinoni et al suggested that decrease in partial pressure of carbon dioxide (PaCO 2 ) (decreased physiologic dead space ratio) with PP is predictive of improved outcome in ARDS [18]. Recently, a study used PaCO 2 instead of oxygenation as a key marker to identify the effects of PP on ARDS patients receiving VV ECMO; they exhibited a significant decrease in PaCO 2 from 39 (34)(35)(36)(37)(38)(39)(40)(41) mmHg to 31 (29)(30)(31)(32)(33)(34)(35)(36)(37) mmHg after a PP session (P = 0.03) without any variation in sweep gas flow [19]. Overall, the exact effect of PP on gas exchange in ARDS patients supported on VV ECMO remains uncertain; rather than oxygenation, PaCO 2 might be an alternative parameter to assess the effect of PP.…”
Section: Gas Exchangementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Gattinoni et al suggested that decrease in partial pressure of carbon dioxide (PaCO 2 ) (decreased physiologic dead space ratio) with PP is predictive of improved outcome in ARDS [18]. Recently, a study used PaCO 2 instead of oxygenation as a key marker to identify the effects of PP on ARDS patients receiving VV ECMO; they exhibited a significant decrease in PaCO 2 from 39 (34)(35)(36)(37)(38)(39)(40)(41) mmHg to 31 (29)(30)(31)(32)(33)(34)(35)(36)(37) mmHg after a PP session (P = 0.03) without any variation in sweep gas flow [19]. Overall, the exact effect of PP on gas exchange in ARDS patients supported on VV ECMO remains uncertain; rather than oxygenation, PaCO 2 might be an alternative parameter to assess the effect of PP.…”
Section: Gas Exchangementioning
confidence: 99%
“…These effects of PP on hemodynamics during ECMO are hardly predictable, suggesting that careful hemodynamic monitoring is needed. Notably, in patients on VV ECMO, conventional methods such as pulmonary artery thermodilution and transpulmonary thermodilution are known to be inaccurate for cardiac output measurement due to indicator loss into the extracorporeal circuit [29][30][31][32]. Transthoracic echocardiography, a bedside noninvasive technique, will play an important role in monitoring cardiac function, and transesophageal echocardiography has been shown to be safe in ARDS patients on VV ECMO despite systemic anticoagulation [33][34][35].…”
Section: Hemodynamicsmentioning
confidence: 99%
“…Other methods measure recirculation via thermodilution or ultrasound dilution techniques 11 , 12 . Those findings are limited in their clinical use because they are based on animal data, fixed cannulation strategies or dual lumen cannulae.…”
Section: Introductionmentioning
confidence: 99%
“…We have read, with great interest, the article by Russ et al . 1 regarding their findings that thermodilution based measurements can overestimate cardiac output during veno-venous extracorporeal membrane oxygenation (ECMO) and that the degree of overestimation correlates with recirculation fraction and the ECMO blood flow (Q EC )/aortic blood flow (Q AO ). Conducting this study in actual lung-injured pigs keeps true to significant confounding factors in patients with acute respiratory distress syndrome.…”
mentioning
confidence: 99%
“…Overall, Russ et al . 1 has provided a very well-conducted study seeking to quantify the inaccuracies of thermodilution based measurements of cardiac output, adding to the original body of evidence. A more comprehensive, and ideally minimally invasive, method is needed to capture true cardiac output.…”
mentioning
confidence: 99%